ChemInform Abstract: Selective Synthesis of 1, 2‐cis‐α‐Glycosides Without Directing Groups. Application to Iterative Oligosaccharide Synthesis. Issue 37 (22nd August 2013) - Chu, An‐Hsiang Adam; Nguyen, Son Hong; Sisel, Jordan A.; Minciunescu, Andrei; Bennett, Clay S.
Abstract A variety of acceptors is applied in the reactions of thioglycosides (I) or (IV), including (II), cholesterol, and mono‐ and disaccharides.